Arab Society: Demographic and Social Trends - Issue No. 17 - United Nations Economic; Social Commission for Western Asia (United Nations, 2025)
The present publication is the latest in a series published biennially by the Statistics, Information Society and Technology Cluster of the Economic and Social Commission for Western Asia (ESCWA). It presents a broad illustration of Arab society and the ways in which it has been changing, focusing on population dynamics, household composition and family formation, housing conditions, health, labour, poverty and inequality, and education. Data are compiled primarily from national statistical offices of ESCWA member States and supplemented by public accessible data from international organizations, such as the International Labour Organization, the World Bank, the United Nations Education, Scientific and Cultural Organization (UNESCO), the United Nations Department of Economic and Social Affairs, the World Health Organization, the Office of the United Nations High Commissioner for Refugees (UNHCR), and the United Nations Relief Works Agency for Palestine Refugees (UNRWA).